THE EFFECT OF RESTRICTED FEEDING AND DIFFERENT OF SLAUGHTERING AGE ON PRODUCTION OF REX RABBIT PELT - Yurniati, Y.; Raharjo, Y.C.; Kusmajadi, S. (Journal of the Indonesian Tropical Animal Agriculture, 2010)
The purpose of this research is to study the interaction between slaughter age and restricted feed, aswell as the influence of each factor on the production of rex rabbits pelt. Randomized Block Designwith Factorial was used in this experiment with the first factor was 3 levels of restricted feedingtreatment where the amount of feed as follow: P1= 100 % from the total feed requirement, P2 = 80%from total feed requirement and P3 = 60% from the total feed requirement. Feed was given in the amountof rabbits requirement, in which 100% of the total requirement was calculated based on body weight(6.7% of body weight in dry matter basis), and second factor was 3 levels of slaughter age (U1= 120 d,U2= 150 d, U3= 180 d) and each treatment was repeated 6 times. The data were analyzed by Anova,and analyzing between the treatments used Contrast Orthogonal. The variable measured were peltproduction (weight pelt, width pelt, thickness dermis and epidermis) of Rex rabbit. There was aninteraction betwen slaughtered age and the amount of feed given to Rex rabbits. Feeding 80% from thetotal feed requirement and the slaughtered age at 150 d were the most efficient in producing pelt of Rexrabbits, with weight 261.0 ± 30.33 g, width 928.0 ± 75.5 cm2, and epidermal thickness 32.50 ± 1.1μ,and dermis 2685.50 ± 15.0 μ.